Silage quality of cultural remains of pineapple pearl with different particle sizes and fermentation times (International Seven Journal of Multidisciplinary, 2023)
The Triângulo Mineiro is responsible for the largest pineapple production in the state of Minas Gerais, and the cultural remains are used as an alternative in animal nutrition. The aim of this study was to assess the quality of pineapple silage produced from the cultural remains of pearl pineapple. A completely randomized design was used in a 4 x 2 factorial scheme, with four fermentation times (30, 60, 90 and 120 days after ensiling) and two particle sizes (20 and 50 mm), and the contents of dry matter (DM), mineral matter (MM), organic matter (OM), crude protein (CP), ether extract (EE), neutral detergent fiber (NDF), acid detergent fiber (ADF), hemicellulose (HEM), total digestible nutrients (TDN), total carbohydrates (TC), non-fibrous carbohydrates (NFC) and pH values were determined. It was observed that the EE content increased by 42% when the silage was stored for 60 days with particle sizes of 50 mm. There was a 7% increase in pH values at 90 days of fermentation for both particle sizes. In the composition of pineapple stubble silage, particle size influenced crude protein, ether extract and pH.